Strong aftershocks traffic light system: A case study of the 8 January 2022 MS6.9 Menyuan earthquake, Qinghai Province, China - Bi, Jinmeng; Yin, Fengling; Jiang, Changsheng; Yin, Xinxin; Ma, Yong; Song, Cheng (Frontiers in Earth Science, 2023)
Strong aftershocks, especially the disaster-causing ones of M≥5.0, which are prone to cause the superimposed effects of earthquake damages, are the key concern to mitigate the seismic risks after large events. However, the real-time and accurate forecasting effects of the traditional probability prediction models based on statistics are usually far less satisfactory. Borrowing an idea from the "Foreshock Traffic Light System" (FTLS), based on the phenomenon of the b-value decreasing or differential stress increasing before strong aftershocks, here we construct a Strong Aftershock Traffic Light System (SATLS) by improving the reliability of time sequence b-value calculation using the data-driven technology and analyzing the b-value variations of strong aftershocks in China continent. And we apply this system to the MS6.9 Menyuan earthquake of January 8, 2022. The earthquake occurrence rates before the largest aftershock (MS5.2) forecasted by the Omi-R-J model are too low, though the model can well forecast aftershock rates for each magnitude interval in most time-periods. However, reliable b-values can be calculated using the Time-sequence b-value Data Driven (TbDD) method. The results show that the b-values continued declining from 1.3 days before the MS5.2 aftershock and gradually recovered after it, which implies that the stress evolution in the focal area can provide clues for the risk alert of strong aftershocks. In the process of building SATLS, the study on 34 M≥6.0 intraplate earthquake sequences in China continent indicates that the differences between the b-values of the aftershock sequence and of the background events, △b=bafter-bbg=±0.1, can be used as thresholds to determine whether M≥5.0 aftershocks would occur. The △b before the MS5.2 aftershock of the MS6.9 Menyuan sequence is about -0.04 obtained using the events before the MS5.2 aftershock, the SATLS yellow alert would be declared, which has some gap to the expected red alert determined by the b-value difference derived from the events included this strong aftershock. To accurately forecast a strong aftershock of M≥5.0, further understanding of the true b-value and a detailed description of the stress evolution state in the source area is demanded.